2005
DOI: 10.1097/01.tp.0000153292.49621.60
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Antibodies in Allograft Rejection: Clinical and Experimental Data

Abstract: The ability of donor-specific major histocompatibility complex alloantibodies to destroy a transplanted organ within minutes, the so-called hyperacute rejection phenomenon, has been known for a long time. It is a clear demonstration of the possible cytotoxic effect of antibodies. Apart from this particular situation, the role of antibodies in inducing acute or chronic allograft rejection remains controversial. Many clinical data have shown that transplant recipients capable of developing class I or class II an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 62 publications
(52 reference statements)
1
43
0
Order By: Relevance
“…Initially, studies that examined the role of antidonor HLA-specific antibodies on outcomes of renal transplantation focused primarily on the pretransplantation setting with the aim of avoiding hyperacute or early antibody-mediated rejection. However, it also is clear that the de novo development of antidonor HLA antibodies after transplantation has deleterious effects on renal allograft survival (56). Given this correlation, efforts to develop methods to inhibit or reverse the formation of new donor-specific antibodies after transplantation are likely to be informative and important.…”
Section: Flow Cytometric Detection Of Intracellular Cytokinesmentioning
confidence: 99%
“…Initially, studies that examined the role of antidonor HLA-specific antibodies on outcomes of renal transplantation focused primarily on the pretransplantation setting with the aim of avoiding hyperacute or early antibody-mediated rejection. However, it also is clear that the de novo development of antidonor HLA antibodies after transplantation has deleterious effects on renal allograft survival (56). Given this correlation, efforts to develop methods to inhibit or reverse the formation of new donor-specific antibodies after transplantation are likely to be informative and important.…”
Section: Flow Cytometric Detection Of Intracellular Cytokinesmentioning
confidence: 99%
“…Many of these patients have had transfusions of blood products, pregnancy, or previous transplants that result in the production of antibody to HLA and the formation of memory B cells (1,2). Transplanted patients with antibodies to HLA have increased rejection episodes and respond poorly to conventional immunosuppression (2)(3)(4)(5). Recent clinical studies suggest that antibodies play a key role in the majority of irreversible acute rejections (6).…”
mentioning
confidence: 99%
“…The first involves alloantibodies binding to donor vascular endothelium, resulting in Ab-mediated vascular rejection via complement activation and ligation of FcRs (26) leading to graft thrombosis. Clinical studies by Rifle et al and others have demonstrated that the presence of high titers of preformed alloantibodies in transplant recipients correlates with complement deposition and poor graft survival (27,28). Rodent studies have demonstrated that the transfer of subthreshold doses of complement-activating Abs into B cell-deficient recipients (C57BL/6 Ig Ϫ/Ϫ ) receiving B10.A (H-2 a ) cardiac allografts restored acute humoral rejection, while the inhibition of the terminal complement activation with anti-C5 mAbs prevented Ab-mediated rejection, leading to long-term graft survival and accommodation (29).…”
mentioning
confidence: 99%